2013
DOI: 10.1038/cdd.2013.29
|View full text |Cite
|
Sign up to set email alerts
|

CREB-binding protein (CBP) regulates β-adrenoceptor (β-AR)−mediated apoptosis

Abstract: Catecholamines regulate the b-adrenoceptor/cyclic AMP-regulated protein kinase A (cAMP/PKA) pathway. Deregulation of this pathway can cause apoptotic cell death and is implicated in a range of human diseases, such as neuronal loss during aging, cardiomyopathy and septic shock. The molecular mechanism of this process is, however, only poorly understood. Here we demonstrate that the b-adrenoceptor/cAMP/PKA pathway triggers apoptosis through the transcriptional induction of the pro-apoptotic BH3-only Bcl-2 family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 62 publications
(80 reference statements)
3
48
0
Order By: Relevance
“…Conversely, MYC dependent suppression of BCLXL and BCL2 sensitizes cells to γ-irradiation-induced apoptosis (Eischen et al, 2001, Maclean et al, 2003). The recent identification of BIM as a transcriptional target of MYC suggests that this BH3-only protein may directly mediate MYC’s pro-apoptotic signal (Campone et al, 2011, Lee et al, 2013). MYC induces BIM accumulation in Burkitt’s Lymphoma and MYC point mutants that fail to induce BIM also fail to induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, MYC dependent suppression of BCLXL and BCL2 sensitizes cells to γ-irradiation-induced apoptosis (Eischen et al, 2001, Maclean et al, 2003). The recent identification of BIM as a transcriptional target of MYC suggests that this BH3-only protein may directly mediate MYC’s pro-apoptotic signal (Campone et al, 2011, Lee et al, 2013). MYC induces BIM accumulation in Burkitt’s Lymphoma and MYC point mutants that fail to induce BIM also fail to induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with our previous finding that activation of PKA by b-AR agonists in fetal thymic organ cultures caused Bim induction and BIM-mediated apoptosis. 12 In the present study, loss of Bim had only limited impact on the induction of apoptosis in several non-hematopoietic tissues, including the Prkar1a deletion induces cachexia in mice L Gangoda et al heart, liver and kidneys. This indicates that other proapoptotic proteins, either on their own or in combination with Bim, might mediate this cell death.…”
Section: Discussionmentioning
confidence: 48%
“…33 In contrast, another report identified Prkar1a as a weak tumour promoter, 9 and our previous work revealed that increased PKA activity can elicit apoptosis, consistent with the notion that PRKAR1a may promote tumorigenesis. 11,12,34 We therefore hypothesized that Prkar1a loss or haploinsufficiency on its own would not be sufficient to promote tumour development. Tumorigenesis does not result from a single oncogenic mutation but is driven by a series of oncogenic lesions, each conferring some growth advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, increased PKA activity has been reported to promote apoptosis by causing transcriptional induction and post-translational stabilization of BIM. 29,34 In line with this, genetic deletion of Prkar1a leads to early embryonic lethality in mice, 35,36 and its inducible loss in diverse adult tissues is reported to trigger PKA activation and apoptosis because of the upregulation of proapoptotic BCL-2 family members. 15 Paradoxically, PKA is also reported to promote cell survival and its hyperactivation causes hereditary endocrine neoplasias.…”
Section: Discussionmentioning
confidence: 94%